The Role of Smaller Towns in Algeria: An Urban and Economic Perspective - Saidi, Feyrouz Ahlam; Saidi, Ikram (Journal for Geography, 2025)
This paper examines the vital role of smaller towns in Algeria’s urbanization, highlighting their influence on national and regional dynamics. As Algeria reflects global urbanization trends, disparities remain between the north and south. Smaller towns—urban centers with populations of 5,000 to 50,000—serve as key links between rural and urban areas, facilitating trade, services, and regional integration. Using census and economic data, the study employs quantitative analysis to evaluate their functions. Despite financial and administrative hurdles, these towns are crucial for promoting regional balance and easing urban concentration. The paper advocates policies to enhance infrastructure, economic opportunities, and services in small towns, emphasizing their significance for sustainable development and for reducing spatial inequalities in Algeria’s growing urban landscape.